Eggs eggs everywhere : teachers guide : preschool-1 - Echols, Jean C.; Hosoume, Kimi.; Kopp, Jaine; GEMS (Project) (Berkeley, CA : Lawrence Hall of Science, University of California at Berkeley, 2002)
A teacher's guide that introduces young children to the wonder of eggs and the story inside eggs from a variety of creatures.
"GEMS.".
Includes bibliographical references.
Professional
Keywords: Eggs -- Study and teaching (Elementary); Embryology -- Study and teaching (Elementary); Embryology -- Study and teaching; Science -- Study and teaching (Elementary); Eggs -- Study and teaching; Science -- Study and teaching